Sistem Pakar Corrective Bay Penghantar Gardu Induk Mekarsari Karawang Dengan Metode Forward Chaining - Agung Nugroho (Teknik Informatika, Universitas Pelita Bangsa, 2021)
The need for electrical and technological energy at this time has grown so rapidly that electrical energy becomes one of the main needs in life. In the course of the substation itself in distributing power supply many disturbances that sometimes disrupt the distribution of electricity in factors such as equipment age and external factors such as lightning and so on. So in need of a system that can help in overcoming the disruption that occurred. The research method used is Quesioner methodology, Interview or Q & A, analysis which includes making flowcharts, and in system design include making State Transition Diagram (STD) and proposed proposal system design (Msukan Design, Process and Output). This study contains about the design of expert systems to find a solution of the disturbances that occur in the bay Deliver by diagnosing the symptoms that arise on the substation. This system is a new system design that is used to find the right disturbance solution, fast, and efficient. The author in this case designed the system by mengguanakan forward chaining method as for this application is made with PHP programming language and using MySQL Database. With this expert system is expected to mengefisiensikan various things such as communication, time and so forth in handling disruptions that occur. Keywords: Expert System, Disturbance, Indication